Secondary Lingular Sleeve Resection to Avoid Pneumonectomy Following Bronchial Anastomotic Dehiscence after Left Lower Lobe Sleeve Resection for Destroyed Lung Syndrome - Bölükbas, Servet; Zanner, Robert; Eberlein, Michael; Biancosino, Christian; Redwan, Bassam (The Surgery Journal, 2018)
Bronchial sleeve resections are technically demanding procedures compared with lobectomies. In case of bronchial anastomotic dehiscence, secondary pneumonectomy is the treatment of choice. However, a secondary pneumonectomy is usually associated with high morbidity and mortality. Here, we first report, to the best of our knowledge, a secondary lingular sleeve resection following bronchial anastomotic dehiscence after left lower lobe sleeve resection in a patient with a destroyed lobe syndrome due to a pseudotumor. This approach enabled the avoidance of secondary pneumonectomy, hence reducing the possible pneumonectomy-associated complications.
Keywords: sleeve resection; anastomotic dehiscence; complication